ANALISIS KELAYAKAN BISNIS FOOD AND BEVERAGE MEEROKET DENGAN METODE BUSINESS MODEL CANVAS DAN ANALISIS SENSITIVITAS - Tasya Angginauli Hanabila, (2022)
Meeroket is a business engaged in the Food & Beverage sector which serves a variety of processed food and beverage menus with the main menu made from noodles. Meeroket is the result of the development of XYZ Noodles business which will be developed in Tangerang. Before running a business, it is necessary to make calculations about the feasibility of the business in terms of aspects such as analysis of projected financial statements (Profit and Loss and Cash Flow), NPV, PP, IRR, and PI. Then, it is reviewed from non-financial aspects such as management and organizational aspects, market aspects, technical and operational aspects, environmental and social aspects, and legal aspects. Furthermore, it is necessary to analyze the sensitivity, namely by projecting profits in several conditions. Based on the results of data processing, it was found that the optimal and moderate conditions that were asked were feasible, while pessimism was declared not feasible. Under optimistic conditions, the NPV is Rp2.022.520.339,56, PP 1 year 8 months, the PI value is 1.30 and the IRR value is 86,996%. in moderate conditions, the NPV was Rp124.934.762,82, PP 4 years and 4 months, the PI value was 1.08 and the IRR value was 8,571%. in pessimistic conditions obtained NPV -Rp1.584.477.858,23, PP more than 5 years, PI value of 0.88 and IRR value of 136,993%. However, those selected in optimistic conditions because they have the largest NPV, PP, IRR, and PI and from a non-financial perspective, Meeroket is also considered feasible.